Trends in stroke thrombolysis rate in Bosnia and Herzegovina: a hospital-based observation study - Marija Bender; Stjepan Čović; Matea Baranik; Sandra Lakičević; Inge Klupka-Sarić (Medicinski glasnik, 2022)
Aim: To assess trends in thrombolysis rates and door-to-needle times in University Hospital Mostar. Methods: Data from the University Hospital Mostar Registry were used. Information on the number of ischaemic stroke patients, intravenous thrombolysis rates and „door-to-needle times“ (DNT) were collected between January 2013 and December 2021. Results: Out of the total of 3100 ischaemic stroke patients, alteplase was given to 130 patients giving a thrombolysis rate of 4.2%. The mean hospital thrombolysis rate increased from 2.4% in 2013 to 10.6% in 2021. Conclusion: Although the hospital thrombolysis rate more than quadrupled, there is still a low proportion of acute ischaemic stroke patients who received intravenous thrombolysis therapy. Education and interventions indicating the importance of recognition and treatment of acute ischemic stoke are necessary for all physicians.
Keywords: alteplase; developing country; door-to-needle times; ischaemic stroke